Multiple‐scattering effects in SAXS and XPCS measurements in the ultra‐small‐angle region. Issue 3 (3rd May 2018) - Semeraro, Enrico F.; Möller, Johannes; Narayanan, Theyencheri
Abstract : An analysis of multiple scattering in ultra‐small‐angle X‐ray scattering (USAXS) and X‐ray photon correlation spectroscopy (XPCS) from a colloidal sample is presented. The high resolution of a pinhole USAXS instrument enabled subtle features of multiple scattering to be resolved. Abstract : An experimental study of the influence of multiple‐scattering events on data acquired by small‐angle X‐ray scattering (SAXS) and X‐ray photon correlation spectroscopy (XPCS) techniques in the ultra‐small‐angle range is presented. Both techniques rely on the single‐scattering assumption and any deviation may lead to erroneous interpretation of structural and dynamical results. Typical effects of multiple scattering on measured static and dynamic scattering from model colloidal suspensions are presented, and it is demonstrated that the same information content as in a single‐scattering experiment can be extracted after applying appropriate corrections. The perturbations induced by multiple scattering on resolution, photon statistics and speckle visibility are evaluated and the required optimal experimental conditions are discussed. In many cases, multiple scattering might be tolerable to a certain extent, especially if any shortcomings are outweighed by beneficial effects from counting statistics, acquisition time and signal‐to‐background ratio. The presented study may help to optimize future experiments and serve as a guide for data evaluation for this type of system.